The association of MTHFR (rs1801133) with hypertension in an indigenous south African population - Mabhida, Sihle E.; Sharma, Jyoti R.; Apalata, Teke; Masilela, Charity; Nomatshila, Sibusiso; Mabasa, Lawrence; Fokkens, Hannah; Benjeddou, Mongi; Muhamed, Babu; Shabalala, Samukelisiwe; Johnson, Rabia (Frontiers in Genetics, 2022)
Aims: The current study sought to investigate the association between the methylenetetrahydrofolate reductase (MTHFR) variant (rs1801133) and the risk of developing hypertension (HTN) in an indigenous South African population. Methods: A total of 442 participants (hypertensive, n = 279 and non-hypertensive, n = 163) from the indigenous tribe residing in Mthatha, Eastern Cape (South Africa) were recruited. HTN was defined as a systolic (SBP) and diastolic blood pressure (DBP) of ≥130/80 mmHg following American Heart Association guidelines. The genotyping of MTHFR (rs1801133) was assessed using MassARRAY® System. Thereafter, the association between rs1801133 in various genetic models and HTN was determined by logistic regression model analysis. Furthermore, the interaction between rs1801133 and selected risk factors on HTN was performed using the open-source multifactor dimensionality reduction (MDR). Results: The low frequency of the T allele (5%) was also observed when compared with the C allele (95%) in both cases and controls. After adjusting for confounding factors (gender, smoking status, BMI, and blood glucose levels), there were no significant associations were observed between rs1801133 and the risk of HTN in all genetic models: genotypic (OR 0.75, 95% CI 0.29–1.95, p = 0.56), dominant (OR 0.86, 95% CI 0.35–2.16, p = 0.75), co-dominant (OR 1.33, 95% CI 0.51–3.48, p = 0.55) and allelic (OR 0.80, 95% CI 0.49–1.62, p = 0.70) in logistic regression analysis. However, a significant interaction was reported among rs1801133, age, and gender (p < 0.0001) with the risk of HTN. Conclusion: The present study reports on the lack of association between MTHFR (rs1801133) and the risk of HTN in an indigenous South African tribe. However, an interaction between gender, age, and rs1801133 was observed. Thus, future studies with a large sample size are required to further validate these findings.